Causes and effects of delays in road construction projects in South Africa - Vahed, Faheem (Department of Construction Economics and Management, 2023)
Delays in road construction projects in South Africa are a common phenomenon. This study aimed at identifying the causes and effects of such delays that are pertinent to South African conditions. The study used a deductive quantitative research approach that used a structured questionnaire developed through a comprehensive literature review on the subject under study and through a pilot evaluation by experts. The structured questionnaire was sent to clients, consultants, contractors, and other external stakeholders involved in SANRAL projects. A total of 64 responses to the questionnaire was received. The data received was analysed using the Relative Importance Index (RII), Kruskal-Wallis Test and Chi-square test. The Cronbach's Alpha was used to measure reliability with the lowest alpha value of 0.827 indicating a high degree of reliability. The RII indicated the top five overall causes of delays in South Africa road construction are: unrest by local communities, stoppages of work by construction mafia/ neighbouring communities/ wards, delays due to regulatory approval processes, poor engagement with local community, and lack of acceptance of project by community. The top five effects of delays that emerged from the survey are: time overruns, cost overruns, disputes and claims between contract parties, stress, and negative social impact/ bad reputation. The study further found that the top five delay minimising measures included: early engagement with the community, improved communication with community, improved management of subcontractors, effective strategic planning by contractor, and timeous payments to contractor and consultant. The Kruskal-Wallis Test revealed that there was no statistically significant difference in the views of all project stakeholders on the five main causes of road construction project delays. There was no statistically significant difference in the views of all project stakeholders on the major effects of road construction project delays. The results of the Kruskal-Wallis test revealed that there is a statistically significant difference in the views of all project stakeholders on the delay minimising measures. The study concludes that project delays occur on road construction projects in South Africa with the major contributor being external-related causes. The study proposed the following recommendations: early involvement of the community in the project through the establishment of community liaison meetings and the establishment of a Public Liaison Committee (PLC), improved management and supervision by the contractor on site, improvement of decision making and approval by client, timeous payment to consultant and contractors by the client, and the contractor should employ improved strategic planning techniques.